2019
DOI: 10.1007/s00265-019-2665-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific responses to simulated territorial intrusions in the common cuckoo: a dual function of female acoustic signaling

Abstract: The two-note call of the male common cuckoo (Cuculus canorus), the so-called "cu-coo", is well known to people as a natural and cultural signal. However, the so-called "bubbling" call of the female cuckoo is almost unknown to most, and its function in the social organization of cuckoos remains understudied. We carried out a study of a possible intraspecific communication function of female bubbling calls, using playbacks to female cuckoos in their natural environment. Regarding vocal responses, both female and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
1
19
1
Order By: Relevance
“…For females, the "bubbling" call may function as a signal to defend resources, for example, host nests. Male cuckoos showing strong responses to playbacks of female "bubbling" call have also been discovered in a recent research (Moskát & Hauber, 2019). Based on these findings, and those of our previous research, which found that vocal activity of female common cuckoos in the same study population peaked in the morning , we suggest that the primary function of the female "bubbling" call in this population is intraspecific communication, rather than distraction of nest hosts.…”
Section: The Function Of the Female "Bubbling" Callsupporting
confidence: 84%
“…For females, the "bubbling" call may function as a signal to defend resources, for example, host nests. Male cuckoos showing strong responses to playbacks of female "bubbling" call have also been discovered in a recent research (Moskát & Hauber, 2019). Based on these findings, and those of our previous research, which found that vocal activity of female common cuckoos in the same study population peaked in the morning , we suggest that the primary function of the female "bubbling" call in this population is intraspecific communication, rather than distraction of nest hosts.…”
Section: The Function Of the Female "Bubbling" Callsupporting
confidence: 84%
“…The female cuckoo's bubbling call seems to be a multifunctional signal, being important in interspecific cuckoo–host relationships, as well as in conspecific communication (Deng et al, 2019; Moskát & Hauber, 2019). The bubbling call might play a role in the context of mate attraction (Moskát & Hauber, 2019; Xia et al., 2019) and could also function as a territorial signal for other conspecific females (Davies, 2015; Moskát et al., 2020). A previous study (York & Davies, 2017) tested an interspecific function of female cuckoo calls against a small host, the reed warbler, while our results revealed that this call also effectively dampened the mobbing responses of a large host, the great reed warbler.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether the female cuckoo's bubbling call (Moskát & Hauber, 2019) has a negative effect on host mobbing intensity, we presented 3D‐printed common cuckoo or dove models as a control to great reed warblers at their nests (following Marton et al., 2019). We performed experimental trials at great reed warbler nests ( n = 61), during the laying and early incubation stages.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations